Kontekstualisasi Makna QS. an-Nur Ayat 4-5 atas Fenomena Tuduhan Perzinaan pada Platform Media Sosial Twitter - Nurlelah Nurlelah; Nurkholidah Nurkholidah; Didi Junaedi; Nurul Bahiyah; Muzaki Muzaki (Gunung Djati Conference Series, 2023)
This study aims to discuss the contextualization of the meaning of QS. an-Nur verse 4-5 on the phenomenon of accusations of adultery on the Twitter social media platform. This research uses a qualitative approach with descriptive-analytic method. The results and discussion in this study indicate that the contextualization of the flogging law contained in QS. an-Nur verses 4-5 on the phenomenon of accusations of adultery that occur on the Twitter social media platform, its enforcement is adjusted to the attitude of the person who accuses and is accused. If the accusation is proven true and the witnesses and conditions are fulfilled, then the flogging law does not apply. Meanwhile, when the accusation is not proven true, the flogging law is adjusted to the wishes of the accused person. In addition, this flogging law must also be applied when the person accused is male, in other words, not only women. This research recommends to all people who utilize technological sophistication, especially the millennial generation, to always be wise in using social media and be careful in using it.